PHENOMENON OF SWARM IN VOLCANIC REGION OF VIETNAM SOUTHMIDDLE SEASHORE - Thuc, Pham Van (Vietnam Journal of Marine Science and Technology, 2009)
From June 2005 up to now in Vietnam Southmiddle Seashore appeared series of earthquakes (swarm) with weak and middle intensities in which there were four felt at Ho Chi Minh city. These earthquakes occurred in the same area where group of active volcanoes are located, at this area Hon Tro volcano group have erupted several times in 1880, 1923 … Swarm shows the movement upward of heat magma flow they will either cause rocks to break or cracks to vibrate and forecasts the the appearance of volcanoes in the future. The characteristics of the earthquakes in this region are that they have magnitude about 5 with the hypocenter depth of about 10 to 12 km and the focal mechanism of strike slip.